Soluble urokinase plasminogen activation receptor and long-term outcomes in persons undergoing coronary angiography - Sommerer, Claudia; Zeier, Martin; Morath, Christian; Reiser, Jochen; Delgado Gonzales de Kleber, Graciela; März, Winfried; Kleber, Marcus E. (Scientific reports, 2019)
Soluble urokinase plasminogen activation receptor (suPAR) is risk factor for kidney disease and biomarker for cardiovascular outcomes but long term longitudinal analyses in a large European cohort have not been perfomed. To hus, we studied suPAR in participants of the Ludwigshafen Risk and Cardiovascular Health study over a very long follow-up time of nearly 10 years. We estimated overall risk of all-cause and cardiovascular death by Cox proportional hazards regression according to quartiles of suPAR, including age, sex, use of lipid-lowering drugs, body mass index, diabetes mellitus, hypertension, smoking, lipids, as well as glomerular filtration rate (eGFR), NT-proBNP, interleukin-6 and high-sensitive CRP as covariates. A total of 2940 participants (age 62.7 ± 10.5years) having a median eGFR of 83.8 mL/min/1.73 m2 were included. The median suPAR concentration was 3010 pg/mL (interquartile range, 2250-3988 pg/mL). Using the lowest quartile of suPAR as the reference, crude hazard ratio for cardiovascular mortality were 1.58 (95% CI 1.16-2.16), 1.85 (95% CI 1.37-2.52) and 2.75 (95% CI 2.03-3.71) in the second, third and fourth quartile, respectively. Adjusting for NT-proBNPeGFR or inflammation (interleukin-6 and high-sensitive CRP) confirmed results. suPAR predicts all-cause and cardiovascular death over a period of ten years in persons undergoing coronary angiography, independent of the natriuretic peptide NT-proBNP, kidney function and of markers of systemic inflammation. Future investigation into a potential causal role of suPAR in cardiovascular disease is warranted.